Providensia Allah Dalam Peristiwa Gempa Palu - Dorman, Atasia Irmansyah; Selan, Yunus (Views : Jurnal Teologi dan Biblika, 2024)
The earthquake that struck Palu on 28 September 2018 was one of the biggest natural disasters in Indonesia, causing devastating impacts, both in terms of casualties and material losses. But behind the tragedy, many saw God's providence, which is God's intervention that is not seen directly but is full of meaning and wisdom. This research aims to examine and reflect on how God's providence was seen in the Palu earthquake, both in terms of finding the meaning behind the event. The method used is a qualitative approach with phenomenological analysis of the experiences and reflections of affected communities. The results showed that although disasters brought suffering, many people felt the presence of God who provided protection, strength and recovery through the events that occurred after the earthquake. The research also highlighted the importance of awareness of God's greatness and sovereignty in the face of natural disasters and how it strengthens the relationship between humans and God, as well as between each other.